School Burnout Inventory: Factorial Validity, Reliability, and Measurement Invariance in a Chilean Sample of High School Students - Carmona-Halty, Marcos; Mena-Chamorro, Patricio; Sepúlveda-Páez, Geraldy; Ferrer-Urbina, Rodrigo (Frontiers in Psychology, 2022)
This brief report assessed the psychometric validity and gender invariance of the School Burnout Inventory (SBI) –a measure of students’ exhaustion, cynicism, and inadequacy– in a convenience sample of 972 high school Chilean students ranging between 12 and 18 years old. The results showed that: (1) the SBI produces adequate scores in terms of reliability; (2) two models (one solution of three related factors and one of second-order and three first-order factors) fitted adequately fit to our sample and was invariant across gender; and (3) the SBI scores were significantly related to other related constructs (i.e., study-related emotions, academic psychological capital, and academic engagement). Overall, the SBI was found to be a reliable and valid inventory to assess school burnout in Chilean high school students.